Integrasi Tri Hita Karana Dalam Manajemen Kurikulum Pada Pengelolaan Pendidikan Paud Hindu di Kota Mataram - Ardika Yasa, I Made (Jurnal Penelitian Agama Hindu, 2025)
This study aims to examine the application of the Tri Hita Karana concept in the management of Hindu Early Childhood Education curricula in Mataram City. The background is grounded in the need to holistically integrate local wisdom and spiritual values into early education. A qualitative descriptive method was employed, with data collected through field observations, in-depth interviews with teachers, school administrators, and parents, and documentary analysis of five selected Hindu institutions. The findings indicate that the three dimensions of Tri Hita Karana Parahyangan (spiritual), Pawongan (social), and Palemahan (environmental) have been systematically integrated into the curriculum structure, learning activities, and assessment practices. This integration strengthens the formation of children’s character in alignment with character education theory and ecological child development frameworks. Key enabling factors include active family involvement, support from local cultural communities, and visionary leadership among teachers. Identified challenges include limited material resources, insufficient specialized teacher training, and national regulations that remain inadequately adaptive. This research provides empirical evidence and proposes a practical model for integrating Tri Hita Karana, offering a pathway for harmonizing national education policies with local cultural values. It contributes to the expanding literature on value-based local education and opens opportunities for developing teacher training modules on Tri Hita Karana, as well as strengthening networks for cultural-educational collaboration.